2022
DOI: 10.3390/vaccines10020176
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness and Burden of Disease for Adjuvanted Quadrivalent Influenza Vaccines Compared to High-Dose Quadrivalent Influenza Vaccines in Elderly Patients in Spain

Abstract: Influenza is a contagious respiratory disease that causes severe illness and death, particularly in elderly populations. Two enhanced formulations of quadrivalent influenza vaccine (QIV) are available in Spain. Adjuvanted QIV (aQIV) is available for those aged 65+ and high-dose QIV (HD-QIV) for those aged 60+. In this study, we used a health economic model to assess the costs and outcomes associated with using aQIV or HD-QIV in subjects aged 65+. Using aQIV instead of HD-QIV to vaccinate an estimated 5,126,343… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 32 publications
(39 reference statements)
2
24
0
1
Order By: Relevance
“…Over the last few decades, vaccination has been a successful public health strategy to prevent various infectious diseases worldwide, effectively helping reduce the burden of vaccine-preventable diseases [1,2]. Influenza is an acute viral infection, highly transmissible, observed around the globe every year, with peak spread during the winter season [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last few decades, vaccination has been a successful public health strategy to prevent various infectious diseases worldwide, effectively helping reduce the burden of vaccine-preventable diseases [1,2]. Influenza is an acute viral infection, highly transmissible, observed around the globe every year, with peak spread during the winter season [3].…”
Section: Introductionmentioning
confidence: 99%
“…Results from a recent modeling exercise across European settings support using enhanced influenza vaccines for the high-risk population (e.g., elderly patients) [7]. Economic modeling studies in Spanish settings have found cell-based QIVs (QIVc) to be cost-effective compared with traditional egg-based QIVs (QIVe) for adult patients (aged 9-64 years and at high-risk of complications) [8]; furthermore, for individuals aged 65 or older, adjuvanted QIV (aQIV) was cost-saving compared with high-dose (HD)-QIV [3], and adjuvanted trivalent influenza vaccine (aTIV) was found to be cost-effective compared with TIV [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…CMI was not explored in this study ( 155 ). Other more recent studies have meanwhile demonstrated that adjuvanted QIV could offer a reduction in costs for society by reducing hospital admissions and deaths compared to a high dose QIV ( 156 , 157 ).…”
Section: Cell-mediated Immunity In (Next-generation) Influenza Vaccin...mentioning
confidence: 99%
“…None of these studies have addressed cost effectiveness—an important factor in determining the overall value of a new vaccine to a community that helps inform decision-making by policy makers and healthcare providers. Using a modeling methodology established in previous studies [ 16 , 17 , 18 , 19 , 20 ], we recently assessed the cost effectiveness of aQIV and HD-QIV and found that aQIV provided cost savings relative to HD-QIV [ 21 ]. Here, we report the results of a similar modeling analysis conducted to evaluate the cost effectiveness of QIVr relative to aQIV.…”
Section: Introductionmentioning
confidence: 99%